2013
DOI: 10.1155/2013/579529
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Nonattendance across the Hepatitis C Disease Course

Abstract: This descriptive qualitative study examined the patient, provider, and institutional factors contributing to nonattendance for hepatitis C (HCV) care throughout the disease course. Eighty-four patients and health and social care providers were interviewed. Thematic analysis of the data yielded 6 interrelated nonattendance themes: self-protection, determining the benefits, competing priorities, knowledge gaps, access to services, and restrictive policies. Factors within the themes varied with the disease course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
4
1
Order By: Relevance
“…Despite a different health system and culture the findings from the research into nonattendance in hepatitis C in Canada (Butt et al, 2013) appear to largely concur with those in this study. However, there appear to be a small number of factors which were not identified in the latter.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Despite a different health system and culture the findings from the research into nonattendance in hepatitis C in Canada (Butt et al, 2013) appear to largely concur with those in this study. However, there appear to be a small number of factors which were not identified in the latter.…”
Section: Discussionsupporting
confidence: 80%
“…However, in contrast to other literature for hepatitis C and related groups where the distance and location are cited as contributing to missed appointments (Hayter, 2005;Morrison et al, 2011;Butt et al, 2013) this research based on the perspectives of clients revealed the complexity of what is meant by a term such as a 'difficult journey'. The factors that made for a difficult journey include: having to get two buses; the timing of the appointment, such as whether it was morning or afternoon; whether the appointment was on a different day to the clients' substitution treatment script; the cost of travel and difficulties with reimbursement; and physical and psychological co-morbidity such as problems with walking and suffering from agoraphobia which for some meant relying on a lift.…”
contrasting
confidence: 72%
See 2 more Smart Citations
“…A major factor for lack of genotyping among those RNA tested was history of drug use. Data from Canada and other countries suggest that lack of knowledge among primary care physicians, especially those not involved in providing care to those with known risk activities, regarding next steps in the cascade and poor knowledge among patients are associated with the gap from HCV diagnosis to RNA testing (Butt et al, 2013, Grebely et al, 2013, Guirgis et al, 2012). Although guidelines and education for primary care physicians are important instruments to bridge this gap, a single blood sample test strategy in which those testing positive for antibody are also tested for RNA (reflex testing) and possibly for genotype could be an effective structural intervention to bridge this gap.…”
Section: Discussionmentioning
confidence: 99%